eHealth 2015 Special Issue: Effects of an assistance service on the quality of life of elderly users - Willner, V.; Schneider, C.; Feichtenschlager, M. (Applied Clinical Informatics, 2015)
Background: The ‘Confidence’ smartphone application aims to support elderly people’s independence as long as possible.Objective: This paper presents first findings on the impact of the system on elderlies’ lives.Methods: 41 end-users tested ‘Confidence’ for six weeks in their daily routine. Before and after the test period the participants assessed their quality of life (QoL). These assessments were analyzed together with additional QoL statements and the usage of ‘Confidence’ which were collected with questionnaires.Results: Six participants assessed their QoL after the trial better than before and six participants assessed it as worse. Five individuals felt that ‘Confidence’ positively influenced their life and these five testers had a positive attitude towards ‘Confidence’ from the start of the trial. After the trial 38 % of the participants said that they felt safer, 37 % communicated more with others, 27 % forgot less, 13 % felt better oriented outside, and 7 % were more on the move due to ‘Confidence’. Three percent said that they were less on the move, two percent felt more unsafe and two percent were less outside.Conclusion: ‘Confidence’ has the potential to affect elderly users’ lives. However, within this analysis positive or negative effects of its usage were not correlated with the QoL assessment. A connection between positive attitude towards technology prior use and a positive impact afterwards was found.Citation: Willner V, Schneider C, Feichtenschlager M. Effects of an assistance service on the quality of life of elderly users. Appl Clin Inform 2015; 6: 429–442http://dx.doi.org/10.4338/ACI-2015-03-RA-0033
Keywords: Aging; assistive technology; quality of life; smartphone